2019
DOI: 10.5811/cpcem.2019.6.43196
|View full text |Cite
|
Sign up to set email alerts
|

Mango Dermatitis After Urushiol Sensitization

Abstract: Prior exposure to poison ivy and poison oak, which are plants in the Anacardiacea family and contain high levels of urushiol, appear to be a risk factor for delayed hypersensitivity reactions to mango fruits. Cross-sensitization between these plants and mangos is believed to be secondary to an overlap in the urushiol antigen and 5-resorcinol, found predominately in mango peels. This unique combination of sensitization and reaction constitutes a type IV hypersensitivity response, mediated and driven by T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Hershko et al [ 97 ] reported the fact the individual with prior exposure to poison ivy/oak allergy may develop allergic contact dermatitis from mango on first exposure. Cross-sensitization of these plants with mango is known to be secondary to a superposition of urushiol antigen and 5-resorcinol, primarily found in mango peels [ 98 ]. These studies overall suggest that mango has some allergic responses, but those reactions have been limited to mango latex, pollen allergen, or prior urushiol exposure [ 99 ].…”
Section: Toxicological/allergenicity Evaluation Of Mlsmentioning
confidence: 99%
“…Hershko et al [ 97 ] reported the fact the individual with prior exposure to poison ivy/oak allergy may develop allergic contact dermatitis from mango on first exposure. Cross-sensitization of these plants with mango is known to be secondary to a superposition of urushiol antigen and 5-resorcinol, primarily found in mango peels [ 98 ]. These studies overall suggest that mango has some allergic responses, but those reactions have been limited to mango latex, pollen allergen, or prior urushiol exposure [ 99 ].…”
Section: Toxicological/allergenicity Evaluation Of Mlsmentioning
confidence: 99%
“…Contact dermatitis can occur on the first exposure to mango due to previous sensitisation to urushiol-containing plants, primarily those in the Anacardiaceae family. Seven patients had previous known sensitisation to poison ivy, poison oak and Lithracea caustica [16,17,31,36,38,40,41]. There was one case where the patient had no known sensitisation to urushiol containing plants, but nevertheless tested positive for urushiol 0.01% in petrolatum at patch testing [28].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 30 patients described above, 23 had been in direct contact with the mango fruit, skin, stem, sap, or even the tree itself [16][17][18]28,36]. The remaining patients had ingested mango either peeled or unpeeled, fresh or processed in the form of mango gelato [1,28,29,31,34,35,[37][38][39][40][41][42]. Patients who had been in direct contact with mango developed skin lesions at contact site, presenting as pruritic and erythematous rash, with occasional vesicles and bullae on the extremities or on the lips, and in the perioral area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to the urushiol in Toxicodendron radicans can cause hypersensitivity in related plants, such as mango, Mangifera indica ( Yoo & Carius, 2019 ), and the Chinese Lacquer Tree, Toxicodendron vernicifluum . Consumer products made from the Chinese Lacquer Tree are manufactured by curing the urushiol-containing sap to a clear, hard, waterproof substance.…”
Section: Introductionmentioning
confidence: 99%